IMPLEMENTASI SENI DALAM PENDIDIKAN ISLAM DI ERA MODERN - Yazida Ichsan; Muhammad Afadh; Muhammad Fatahillah; Adam Baustin Erlangga (LP3M IAI Al-Qolam Malang, 2021)
This research focus on studying the art based on Islamic perspective. The aim of this research is to understand Islamic perspective towards the art. Besides to develop the concept of art in the religion aspect, it also to understand the implementation of art towards the Islamic education. By using descriptive method, this study also analyze certain phenomenon in the present or past. Researchers conduct trusted resources of books and articles in the internet to be reviewed comprehensively. It is conducted to draw certain conclusion to give us new horizon about Islamic perspective towards art. Key words: art, Islam, education, implementation, modern.